Large-aperture nano silicon dioxide composite material and preparation method thereof

By optimizing the pore size and preparation method of nano -nanoxide materials, the development of large -pore nano -nano -nanoxide composite materials is developed, combined with liquid and solid lubricants, solving the performance limitations of existing liquid lubricants in the special application scenarios and the interior holes Silicon dioxide cannot carry the problem of solid nanoparticles, realizing excellent friction learning and lubrication performance, and is suitable for a variety of mechanical applications.

CN119372004AActive Publication Date: 2025-01-28LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411501274.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Existing liquid lubricants have performance limitations in special application scenarios such as oil-free, high and low temperatures, anti-corrosion, anti-fouling, and radiation-proofing. Especially in space environments, they are prone to degradation and thickening, carbonization and degradation and drying, creeping loss and leakage. etc. At the same time, the pore size of mesoporous silica material is small and cannot effectively support solid nanoparticle lubricant.

Method used

By optimizing the pore size and preparation methods of nano -nanoxide materials, the large -pore nano -nano -nano -sanxia composite material is developed, combined with liquid lubricants and solid nanoparticles lubricants, forming composite materials with excellent friction and lubrication performance.

Benefits of technology

The application requirements in the field of self -lubrication have good corrosion resistance, environmental adaptability, self -lubrication performance, low density and high ratio strength, which can be widely used in the fields of automotive industry and high -end technology equipment, reducing wear and friction coefficients , Improve mechanical efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of nano composite materials, and particularly relates to a large-aperture nano silicon dioxide composite material and a preparation method thereof. The large-aperture nano silicon dioxide composite material comprises nano large-aperture silicon dioxide and a lubricating additive loaded in the silicon dioxide material, the particle size of the nano large-aperture silicon dioxide is 50-110 nm, and the aperture of the nano large-aperture silicon dioxide is 3-30 nm. According to the invention, the raw materials and the preparation process are optimized and adjusted, so that the lubricating oil has excellent tribological performance and lubricating performance, and can meet the application requirements of the lubricating oil in the self-lubricating field. The preparation method has the advantages of simple raw materials, mild process conditions, no need of complex equipment, and very convenient industrial production. The preparation method is simple to operate, low in production cost and suitable for industrial production; and the prepared product has certain stability, excellent lubricating property and wide application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano composite materials, and in particular relates to a large-pore nano silicon dioxide composite material and a preparation method thereof. Background Art

[0002] Friction is a common phenomenon in daily life. It is inevitable in motion systems. Adding lubricants between the friction contact surfaces in relative motion is an effective way to reduce friction and wear, which effectively avoids unnecessary material loss and economic losses caused by friction.

[0003] In addition, adding lubricants between the interacting dual surfaces can play a role in bearing loads, reducing the friction coefficient between the dual surfaces, and reducing the wear of the dual surface materials. Among them, liquid lubricants are the largest and most diverse type of lubricants. They can easily form a fluid dynamic film on the dual surfaces, hindering the direct contact of the friction pairs, and have good heat dissipation and flushing effects. However, existing liquid lubricants still cannot get rid of performance limitations when used in special application scenarios such as oil-free, high and low temperature, corrosion resistance, anti-fouling, and radiation protection. Especially when used in space environments, they are prone to degradation and thickening, carbonization and degradation and drying, creep loss, and leakage.

[0004] Nano-silicon dioxide materials as lubricant additives can effectively improve the comprehensive performance of lubricants. On the one hand, it can form a thin film with a low friction coefficient on the friction surface to fill and repair the friction surface. On the other hand, its small size and spherical shape can play the role of micro-bearings and polish and strengthen the friction surface, effectively improving the lubricant's load-bearing capacity and anti-friction and anti-wear properties, which is conducive to broadening the application of lubricants under harsh working conditions such as heavy loads and high temperatures.

[0005] In the previous research work, the inventors prepared a hierarchical porous silica material doped with boron in situ by the template method, and it significantly improved the lubrication performance of the lubricant as a lubricant additive (Chinese patent CN116715246A). In addition, the inventors also stored the lubricant in mesoporous silica nanoparticles with an average pore size of 12.8nm (Chinese patent CN115948191A). Thanks to the rich mesoporous structure of silica, the lubricant stored in the pores can be released to the friction dual surface under the action of applied load and friction heat to play a lubricating role, avoiding the problem of lubricant being easily deteriorated under atomic oxygen or proton irradiation when used in a space environment, resulting in a short service life of the lubricant.

[0006] However, due to the small pore size of mesoporous silica, the types of lubricants that can be stored are limited by the viscosity and type of lubricating oil. In particular, for solid nanoparticle lubricants such as copper nanoparticles, molybdenum disulfide nanoparticles, copper sulfide nanoparticles, etc., they cannot be injected into the pores of mesoporous silica materials due to the limitation of the particle size of the nanoparticles.

[0007] Therefore, based on the literature (Yang YN, Wan JJ, Niu YT, Gu ZY, Zhang J, Yu MH. Structure-dependent and glutathione-responsive biodegradable dendritic mesoporous organosilica nanoparticles for safe protein delivery. Chem Mater 28(24): 9008-9016(2016)), the present invention adjusts and optimizes the pore size of mesoporous silica and the preparation method of the composite material, in order to obtain a nano-silica composite self-lubricating material with excellent performance. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a large-pore nano-silicon dioxide composite material and a preparation method thereof, which optimizes and adjusts the raw materials and the preparation process so that it has excellent tribological properties and lubrication properties, and can meet its application requirements in the field of self-lubrication.

[0009] The invention also provides application of the large-pore nano-silicon dioxide composite material.

[0010] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0011] A large-pore nano-silica composite material comprises nano-large-pore silica and a lubricating additive loaded in the nano-large-pore silica; the nano-large-pore silica has the advantages of small particle size, large pore size, high specific surface area and pore volume, and strong adsorption capacity; its rich pore structure has good storage capacity and certain stability; it has excellent lubrication performance and a wide range of applications.

[0012] The large-pore nano-silicon dioxide composite material of the present invention has the advantages of good corrosion resistance, excellent environmental adaptability, good self-lubricating performance, low density and high specific strength, etc. As a solid self-lubricating material, it has been widely used in the automotive industry and high-end technical equipment and other fields. For example, it is used to manufacture mechanical parts such as bearings, gears, seals, guide wheels, etc., to reduce wear and friction coefficient and improve mechanical efficiency.

[0013] Specifically, the nano-sized macroporous silica has a particle size of 50 to 110 nm and a pore size of 3 to 30 nm.

[0014] Specifically, the large-pore nano-silicon dioxide composite material is prepared from a silicon source, a template agent, a pore-enlarging agent, an organic amine catalyst, water, anhydrous ethanol, and a lubricating additive.

[0015] Specifically, the silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, trimethoxysilane and sodium silicate, preferably ethyl orthosilicate.

[0016] Specifically, the template agent is one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate and sodium dodecylsulfonate; preferably sodium dodecylbenzenesulfonate.

[0017] Specifically, the pore expanding agent is one or more of sodium salicylate, tributyl phosphate, and diethyl phthalate, and sodium salicylate is more preferred.

[0018] Specifically, the organic amine catalyst is one or more of octylamine, dodecylamine, ethanolamine, diethanolamine and triethanolamine, and triethanolamine is more preferred.

[0019] Specifically, the lubricating additive is a liquid lubricant and / or a solid nanoparticle lubricating material.

[0020] Specifically, the liquid lubricant includes one or more of base oil, plant-based lubricating oil, ionic liquid, and perfluoropolyether lubricating oil.

[0021] Further preferably, the liquid lubricant is an ionic liquid [DBUH + ][9C - ]、TIPA C 11 or [DBNH + ][18C - ].

[0022] Specifically, the solid nanoparticle lubricating material is one or more of copper nanoparticles, copper sulfide nanoparticles, molybdenum disulfide nanoparticles, and ferrosoferric oxide nanoparticles.

[0023] Furthermore, the present invention also provides a method for preparing a macroporous nano-silicon dioxide composite material, comprising the following steps:

[0024] (1) dissolving the template agent and the pore-enlarging agent in water, and stirring the reaction at a certain temperature to obtain an organic composite template suspension;

[0025] Adding an organic amine catalyst to the suspension, stirring and reacting for a period of time, then adding a silicon source, stirring and reacting for a period of time, allowing the reaction system to naturally cool to room temperature (25±5° C.), adding anhydrous ethanol, stirring and reacting for a period of time, then standing to obtain a mixed solution;

[0026] (2) centrifuging the mixed solution in step (1), washing and drying the solid product, and calcining it in a muffle furnace to remove the organic composite template, thereby obtaining mesoporous nano-silica;

[0027] (3) soaking or impregnating the mesoporous nano-silica and the solution of the lubricating additive or the dispersion of the lubricating additive under vacuum for a period of time, then removing the excess anhydrous ethanol by rotary evaporation, and drying to obtain a large-pore nano-silica composite material.

[0028] Specifically, in step (1), the silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, trimethoxysilane and sodium silicate, preferably ethyl orthosilicate.

[0029] Specifically, in step (1), the template agent is one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, sodium dodecylbenzene sulfonate and sodium dodecyl sulfonate; preferably sodium dodecylbenzene sulfonate.

[0030] Specifically, in step (1), the pore expanding agent is one or more of sodium salicylate, tributyl phosphate, and diethyl phthalate, and more preferably sodium salicylate.

[0031] Specifically, in step (1), the organic amine catalyst is one or more of octylamine, dodecylamine, ethanolamine, diethanolamine and triethanolamine, and triethanolamine is more preferred.

[0032] Specifically, in step (3), the lubricating additive is a liquid lubricant and / or a solid nanoparticle lubricating material.

[0033] Specifically, the liquid lubricant includes one or more of base oil, plant-based lubricating oil, ionic liquid, and perfluoropolyether lubricating oil.

[0034] Further preferably, the liquid lubricant is an ionic liquid [DBUH + ][9C - ]、TIPA C 11 or [DBNH + ][18C - ].

[0035] Specifically, the solid nanoparticle lubricating material is one or more of copper nanoparticles, copper sulfide nanoparticles, molybdenum disulfide nanoparticles, and ferrosoferric oxide nanoparticles.

[0036] Specifically, in step (1), the reaction temperature of the template agent and the pore-enlarging agent is 60-80° C., and the stirring reaction time is 0.5-2 h, preferably 1-2 h, and more preferably 2 h.

[0037] Specifically, in step (1), the mass ratio of the silicon source to the template is preferably 10-80:5-10, and more preferably 25-65:6-10.

[0038] Specifically, in step (1), the mass ratio of the silicon source to the pore expanding agent is preferably 20-80:1-6, and more preferably 25-65:1-5.

[0039] Specifically, in step (1), the mass ratio of the silicon source to the organic amine catalyst is preferably 20-75:1-3, preferably 25-65:1.5-2.5, and more preferably 45-50:1.9-2.

[0040] Specifically, in step (1), after adding the organic amine catalyst to the suspension, the stirring reaction time is 0.5 to 2 hours, preferably 1 to 2 hours, and more preferably 1 to 1.5 hours, and the reaction temperature is 70 to 90°C, preferably 60 to 85°C, and more preferably 75 to 85°C.

[0041] Specifically, in step (1), after adding the silicon source to the suspension, the stirring reaction time is 1 to 4 hours, preferably 2 to 3 hours, and the reaction temperature is 70 to 90°C, preferably 60 to 85°C, and more preferably 75 to 85°C; the silicon source is added by slow dropwise addition, preferably by slow dropwise addition through a constant pressure funnel.

[0042] Specifically, in step (1), after the reaction system is naturally cooled to room temperature (25±5°C), when anhydrous ethanol is added, the mass ratio of anhydrous ethanol to silicon source is preferably 4-20:1-3, preferably 5-15:1.5-2.5; the stirring reaction time after adding anhydrous ethanol is 0.5-1h, preferably 0.5h.

[0043] Specifically, in the preparation method of the present invention, the cooling method is natural cooling.

[0044] Specifically, in step (2), washing is performed with water and / or anhydrous ethanol, and the number of times of washing with anhydrous ethanol is 3 to 5 times, more preferably 3 to 4 times;

[0045] The water washing is performed 3 to 5 times, more preferably 3 to 4 times.

[0046] Specifically, in step (2), the washing with anhydrous ethanol is preferably carried out under centrifugal conditions, the rotation speed during centrifugation is 3000-8000 rpm, more preferably 4000-6000 rpm, and the centrifugation time is preferably 5-10 min.

[0047] Specifically, in step (2), the water washing is preferably carried out under centrifugal conditions, the rotation speed during centrifugation is 3000-8000 rpm, more preferably 4000-6000 rpm, and the centrifugation time is preferably 5-10 min.

[0048] Specifically, in step (2), the drying method is heat drying or freeze drying, and heat drying is more preferred.

[0049] Specifically, in step (2), the drying temperature is 50 to 90° C., preferably 60 to 80° C., and the drying time is 10 to 24 hours, preferably 10 to 12 hours, and more preferably 11 to 12 hours.

[0050] Specifically, in step (2), the calcination temperature is 450-650°C, preferably 500-650°C, and more preferably 550°C.

[0051] Specifically, in step (2), the calcination time is started from when the temperature reaches the calcination temperature, and the calcination time is 3 to 7 hours, more preferably 4 to 6 hours, and even more preferably 5 hours.

[0052] Specifically, in step (2), during calcination, the temperature is increased from room temperature (25±5°C) to the calcination temperature at a rate of 5 to 15°C / min, more preferably 10°C / min.

[0053] Preferably, the calcination is carried out in a muffle furnace; the calcination atmosphere is preferably air.

[0054] Specifically, in step (3), the solution of the lubricating additive or the dispersion of the lubricating additive is an anhydrous ethanol solution of the lubricating additive or an anhydrous ethanol dispersion of the lubricating additive.

[0055] Specifically, in step (3), the mass ratio of the mesoporous nano-silica to the solution of the lubricating additive is 1:0.5-10, more preferably 1:0.5-6, and even more preferably 1:3-6.

[0056] Specifically, in step (3), the ratio of the dispersion of the mesoporous nano-silica and the lubricating additive is 1 g: (1.5-8) mL, and more preferably 1 g: (1.6-6) mL.

[0057] Preferably, the concentration of the solution of the lubricating additive is 2-8% (w / v), preferably 5% (w / v).

[0058] Preferably, the concentration of the dispersion of the lubricating additive is 0.1 to 0.5 g / mL, preferably 0.2 g / mL.

[0059] Specifically, in step (3), the immersion method is preferably vacuum immersion, and the vacuum degree of the vacuum immersion is -0.08 to -0.1 MPa, and more preferably -0.1 MPa; the immersion temperature is preferably room temperature (25±5°C), and the immersion time is 3 to 6 hours, and more preferably 4 to 5 hours.

[0060] Specifically, in step (3), the impregnation method is preferably vacuum impregnation, the vacuum degree of the vacuum impregnation is -0.08 to -0.1 MPa, and more preferably -0.1 MPa; the impregnation temperature is preferably room temperature (25±5°C), and the impregnation time is 3 to 6 hours, and more preferably 4 to 5 hours.

[0061] Specifically, in step (3), the lubricating additive remaining on the surface of the composite self-lubricating material can also be removed by washing.

[0062] Specifically, in step (3), the drying temperature is preferably 50 to 80° C., more preferably 60 to 80° C.; the drying time is preferably 8 to 24 hours, more preferably 11 to 13 hours.

[0063] Furthermore, based on a general inventive concept, the present invention also provides the use of the large-pore nano-silicon dioxide composite material in the preparation of lubricants for the automotive industry or high-end equipment.

[0064] Further preferably, based on a general inventive concept, the present invention also provides the use of the large-pore nano-silicon dioxide composite material in the preparation of lubricants for mechanical parts such as bearings, gears, seals, guide wheels, etc.

[0065] Furthermore, the present invention also provides a method for testing the performance of the macroporous nano-silicon dioxide composite material, which specifically comprises the following steps:

[0066] The large-pore nano-silicon dioxide composite material is mixed with a water-alcohol system solvent, and then a dispersant is added, and then the tribological properties of the prepared large-pore nano-silicon dioxide composite material are tested.

[0067] Specifically, the water-alcohol system is a mixed solvent of water and alcohol, and the mass ratio of the two is 1-2:2-1, and more preferably 1:1; the alcohol is one or more of polyethylene glycol 400, polyethylene glycol 800, 1,3-propylene glycol and ethylene glycol, and more preferably polyethylene glycol 800.

[0068] Specifically, the mass ratio of the macroporous nano-silica composite material to the water-alcohol system solvent is 1:(800-1000), preferably 1:1000.

[0069] Specifically, the dispersant is sodium lauryl sulfate.

[0070] Specifically, the mass ratio of the large-pore nano-silicon dioxide composite material to the dispersant is 1:(15-20), preferably 1:20.

[0071] Specifically, during the tribological performance test, the load is one or more of 98N, 196N and 392N, and more preferably 196N;

[0072] During the tribological performance test, the rotation speed is one or more of 900 r / min, 1200 r / min and 1450 r / min, and more preferably 1450 r / min;

[0073] When testing the tribological properties, the test time is 10 to 30 minutes, more preferably 30 minutes.

[0074] Alternatively, as another preferred technical solution, the method for testing the performance of the macroporous nano-silicon dioxide composite material of the present invention specifically comprises the following steps:

[0075] The macroporous nano-silicon dioxide composite material is mixed with a binder, and then stirred at 40° C. to 50° C. for 0.5 to 2 hours to form a suspension;

[0076] Then, a curing agent is added to the suspension, and after stirring for 2 to 5 minutes, the suspension is defoamed and then cured at room temperature (25±5° C.) for 1 to 3 hours and then at 70° C. to 90° C. for 10 to 15 hours to obtain a polymer. The tribological properties of the obtained polymer are then tested.

[0077] Specifically, the binder is epoxy resin.

[0078] Specifically, the mass ratio of the large-pore nano-silica composite material to the binder is 1:(5-12), preferably 1:10 or 1:5.

[0079] Specifically, the curing agent is triethylenetetramine.

[0080] Specifically, the mass ratio of the suspension to the curing agent is (6-10):1.

[0081] Specifically, during the tribological performance test, the load is one or more of 15N, 20N and 25N, and more preferably 15N;

[0082] Specifically, during the tribological performance test, the test time is 30 to 60 minutes, more preferably 60 minutes.

[0083] The preparation method provided by the present invention uses a complex formed by the interaction of an ionic surfactant and an ionic organic pore-enlarging agent as a template, and under the catalytic action of an organic amine, a silicon source undergoes a hydrolysis and polycondensation reaction at the template, and after high-temperature calcination to remove the template, obtains silicon dioxide nanoparticles with a large pore size; the present invention mixes the prepared nano large-pore silicon dioxide with a lubricating additive, and obtains a large-pore nano silicon dioxide composite material carrying the lubricating additive by soaking or impregnation treatment under a vacuum state.

[0084] Compared with the prior art, the advantages of the present invention are:

[0085] The macroporous nano-silicon dioxide composite material provided by the invention comprises nano macroporous silicon dioxide and a lubricating additive dispersed in the silicon dioxide material.

[0086] The large-pore nano-silica composite material provided by the present invention has a regular spherical morphology, a high specific surface area and pore volume, good chemical and thermal stability, and can carry a rich variety of lubricants with a high loading amount; the large-pore nano-silica composite material of the present invention combines the high mechanical strength and high wear resistance of silica nanoparticles with the low friction of lubricants, has a long life, low friction and good service reliability, and can meet the requirements for low friction and high wear resistance of materials under harsh working conditions.

[0087] The present invention utilizes the rich pore structure and large pore size of nano-sized large-pore silica to make the material not limited by the viscosity of the lubricant when carrying a liquid lubricant. In addition, the rich large pores in silica can also carry a variety of solid nano-lubricants, and its pore structure can make the solid nano-lubricants evenly distributed in silica, avoiding agglomeration of nano-particles due to their small size.

[0088] The preparation method of the present invention has simple raw materials, mild process conditions, no need for complex equipment, and is very convenient for industrial production. The preparation method of the present invention is simple to operate, has low production cost, and is suitable for industrial production; the prepared product has certain stable performance, excellent lubrication performance, and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] Figure 1 This is a transmission electron microscope image of the oil-carrying macroporous nano-silicon dioxide composite material described in Example 1;

[0090] Figure 2 The nitrogen adsorption-desorption isotherm and BJH pore size distribution diagram of the oil-carrying macroporous nano-silica composite material described in Example 1, wherein: Figure 2(a) is the nitrogen adsorption-desorption isotherm, Figure 2 (b) is the BJH pore size distribution diagram;

[0091] Figure 3 Thermogravimetric diagram of the oil-carrying macroporous nano-silica composite material obtained in Example 1-3;

[0092] Figure 4 It is a comparison chart of four-ball friction data of Example 1 and Comparative Example 1;

[0093] Figure 5 It is a comparison chart of four-ball friction data of Example 2 and Comparative Example 1;

[0094] Figure 6 It is a comparison chart of four-ball friction data of Example 3 and Comparative Example 1;

[0095] Figure 7 The tribological performance comparison diagram of Example 4 and epoxy resin;

[0096] Figure 8 is a hardness data diagram of Example 4 and epoxy resin;

[0097] Fig. 9 The contact angle data of Example 4 and epoxy resin are shown in FIG.

[0098] Fig.10 is a comparison chart of the tribological properties of Example 5 and epoxy resin;

[0099] Fig.11 is a hardness data diagram of Example 5 and epoxy resin;

[0100] Fig.12 This is the contact angle data diagram of Example 5 and epoxy resin. DETAILED DESCRIPTION

[0101] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0102] Unless otherwise specified, the instruments and equipment used in the following examples are all commercially available conventional instruments and equipment; other reagents and materials used are all commercially available conventional reagents and materials unless otherwise specified. The experimental methods involved in the following examples are all conventional methods unless otherwise specified.

[0103] The room temperature in the following examples refers to 25±5°C.

[0104] The ionic liquids used in the following examples [DBUH+ ][9C - ]、TIPA C 11 、[DBNH + ][18C - ] are prepared as follows (references for the preparation methods of three ionic liquids Yang SH, Shi YJ, Zuo XY, Zhang X. Tribological properties of the P and S-free protic ionic liquids as water-based lubricants, Journal of Molecular Liquids 414: 126101 (2024)):

[0105] 1. [DBUH + ][9C - Preparation of

[0106]

[0107] Nonanoic acid and DBU (1,8-diazabicyclo[5.4.0]undec-7-ene) are mixed in an equimolar ratio (nonanoic acid and DBU molar ratio is 1:1, DBU is generally used in an amount of 0.03-0.05 mol, and the amount used here is 0.04 mol), and an appropriate amount (20-30 ml) of methanol is used as a solvent, and stirred evenly at 25°C for 12 hours. Then the obtained mixture is rotary evaporated at 40°C for 4 hours, and then placed in a 40°C vacuum drying oven (vacuum degree of -0.1 MPa) for 6 hours to remove the excess methanol solvent that has not evaporated, and the obtained product is obtained.

[0108] 2. [DBNH + ][18C - Preparation of

[0109]

[0110] Octadecanoic acid and DBN (1,5-diazabicyclo[4.3.0]-5-nonene) are mixed in an equal molar ratio (the molar ratio of octadecanoic acid to DBN is 1:1, the general amount of DBN is 0.03-0.05 mol, and the amount used here is 0.04 mol), and an appropriate amount (20-30 ml) of methanol is used as a solvent, and stirred evenly at 25°C for 12 hours. Then the obtained mixture is rotary evaporated at 40°C for 4 hours, and then placed in a 40°C vacuum drying oven (vacuum degree of -0.1 MPa) for 6 hours to remove the excess methanol solvent that has not evaporated, and the obtained product is obtained.

[0111] 3. TIPA C 11 Preparation

[0112]

[0113] Undecanoic acid and triisopropanolamine are mixed in an equimolar ratio (the molar ratio of undecanoic acid to triisopropanolamine is 1:1, the general amount of triisopropanolamine is 0.03-0.05 mol, and the amount used here is 0.04 mol), and an appropriate amount (20-30 ml) of acetonitrile is used as a solvent, and stirred evenly at 80° C. for 12 hours. The obtained mixture is then rotary evaporated at 40° C. for 4 hours, and then placed in a 40° C. vacuum drying oven (vacuum degree of -0.1 MPa) for 6 hours to remove the excess acetonitrile solvent that has not evaporated, and the obtained product is obtained.

[0114] Comparative Example 1

[0115] 0.4 g of dispersant (sodium dodecyl sulfate) was added to 20 g of water / polyethylene glycol 800 mixed solvent (the mass ratio of the two in the mixed solvent was 1:1); then the tribological properties of the obtained product were tested using a four-ball friction tester (MS-10A). The test conditions were room temperature (25±5°C), load 196N, speed 1450r / min, and time 30min.

[0116] Example 1

[0117] Embodiment 1 provides a large-pore nano-silicon dioxide composite material, comprising nano-large-pore silicon dioxide and a liquid lubricant located in the pore structure of the silicon dioxide material. The preparation method of the large-pore nano-silicon dioxide composite material comprises the following specific steps:

[0118] 1) 9.5 g of sodium dodecylbenzene sulfonate and 4.2 g of sodium salicylate were dissolved in 625 g of water, stirred and heated to 80° C. for reaction for 2 h to obtain an organic composite template suspension; then 1.90 g of triethanolamine was added, stirred for 1 h, and 46.7 g of ethyl orthosilicate was slowly added dropwise using a constant pressure funnel, and stirring was continued for 2 h; naturally cooled to room temperature (25±5° C.), 235 g of anhydrous ethanol was added, stirred for 30 min, and then allowed to stand; the obtained solution was centrifuged, and then washed with water and ethanol for 3 times (the speed of a single centrifugal washing was 6000 rpm and the time was 10 min), and the obtained product was dried at 60° C. for 12 h, and then placed in a muffle furnace and calcined at 550° C. for 5 h; the calcined product was ground into powder to obtain mesoporous nano-silica;

[0119] 2) The ionic liquid [DBUH + ][9C - ] was dissolved in anhydrous ethanol to prepare [DBUH + ][9C - ]Ethanol solution, for later use;

[0120] The mesoporous nano-silica obtained in step 1) is placed in an ionic liquid [DBUH + ][9C - ] in an ethanol solution with a mass ratio of 1:5. After being immersed in a vacuum state (vacuum degree of -0.1MPa) for 4h, the mixture was subjected to rotary evaporation for 6h to remove excess ethanol, and then dried in a blast oven at 60°C for 12h to obtain an oil-loaded macroporous nano-silica composite material, which was recorded as SiO2-DBUH 9C.

[0121] The ionic liquid used in Example 1 is [DBUH + ][9C - ], the structural formula is as follows:

[0122]

[0123] Figure 1 This is a transmission electron microscope image of the oil-carrying macroporous nano-silicon dioxide composite material described in Example 1. Figure 1 It can be seen that silica has a regular spherical morphology, a particle size of 90 to 110 nm, and a large number of radial mesoporous channel structures inside the particles.

[0124] Figure 2 The nitrogen adsorption-desorption isotherm (a) and the corresponding pore size distribution diagram (b) of the oil-carrying macroporous nano-silica composite material described in Example 1 are shown in FIG. Figure 2 It can be seen that the silica particles have a mesoporous structure of 3 to 20 nm, and the specific surface area and pore volume of the material are 625 m 2 / g and 1.9cm 3 / g.

[0125] The performance test of the oil-carrying macroporous nano-silicon dioxide composite material prepared in Example 1 was carried out, and the same test was carried out in Comparative Example 1. The specific method is as follows:

[0126] 0.02g of SiO2-DBUH 9C was added to 20g of a mixed solvent of water / polyethylene glycol 800 (the mass ratio of the two in the mixed solvent was 1:1), and then 0.4g of a dispersant (sodium dodecyl sulfate) was added; then the tribological properties of the prepared large-pore nano-silica composite material were tested using a four-ball friction tester (MS-10A), and the steel ball used in the test was a GCr15 bearing steel ball with a diameter of φ=12.7mm. The test conditions were room temperature (25±5℃), load 196N, speed 1450r / min, and time 30min.

[0127] Test results:

[0128] Figure 4 The friction data results of Example 1 and Comparative Example 1 are shown in FIG. Figure 4It can be seen that the friction coefficient of comparative example 1 is 0.015 in the early stage and about 0.012 in the later stage. After adding the oil-carrying large-pore nano-silicon dioxide composite material SiO2-DBUH 9C, the friction coefficient is significantly reduced to 0.010.

[0129] Example 2

[0130] Example 2 provides a large-pore nano-silicon dioxide composite material. In the preparation method of the large-pore nano-silicon dioxide composite material in Example 2, step 1) is the same as in Example 1. The difference between Example 2 and Example 1 is that in step 2), the ionic liquid [DBUH + ][9C - ] replaced by TIPA C 11 The obtained oil-loaded macroporous nano-silica composite material is denoted as SiO2-TIPA C 11 .

[0131] The ionic liquid used in Example 2 is TIPA C 11 , the structural formula is as follows:

[0132]

[0133] The performance test of the oil-carrying large-pore nano-silicon dioxide composite material prepared in Example 2 was carried out under the same test conditions as in Example 1, and the same test was carried out on Comparative Example 1.

[0134] Test results:

[0135] Figure 5 The friction data of Example 2 and Comparative Example 1 show that the friction coefficient of Comparative Example 1 is 0.015 in the early stage and about 0.012 in the later stage. 11 After that, the friction coefficient is significantly reduced to 0.010.

[0136] Example 3

[0137] Example 3 provides a large-pore nano-silicon dioxide composite material. In the preparation method of the large-pore nano-silicon dioxide composite material in Example 3, step 1) is the same as in Example 1. The difference between Example 3 and Example 1 is that in step 2), the ionic liquid [DBUH + ][9C - ] is replaced by [DBNH + ][18C - ], and the obtained oil-loaded macroporous nano-silica composite material was denoted as SiO2-DBNH 18C.

[0138] The ionic liquid used in Example 3 is [DBNH +][18C - ], the structural formula is as follows:

[0139]

[0140] The performance test of the oil-carrying large-pore nano-silicon dioxide composite material prepared in Example 3 was carried out under the same test conditions as in Example 1. Meanwhile, the same test was carried out on Comparative Example 1.

[0141] Test results:

[0142] Figure 6 The friction data results of Example 3 and Comparative Example 1 show that the friction coefficient of Comparative Example 1 is 0.015 in the early stage and about 0.012 in the later stage. After adding the oil-carrying large-pore nano-silica composite material SiO2-DBNH 18C, the friction coefficient is significantly reduced to 0.010.

[0143] Example 4

[0144] Example 4 provides a large-pore nano-silicon dioxide composite material, comprising nano-large-pore silicon dioxide and a solid nano-particle lubricating material located in the pore structure of the silicon dioxide material. In the preparation method of the large-pore nano-silicon dioxide composite material, step 1) is the same as that of Example 1. The difference between Example 4 and Example 1 is that:

[0145] Step 2) is: dispersing copper nanoparticles (preparation method reference Hua KY, Shi YJ, Tang MM, Zuo XY, Gao J, Zhang X. In-situ surface modified water-soluble Cu nanoparticles as lubrication additives in water-based cutting fluids. Colloid Surfaces A 698: 134605-134615 (2024)) in anhydrous ethanol to prepare a copper nanoparticle dispersion with a concentration of 0.2 g / ml for standby use; the copper nanoparticles described in this embodiment are used as solid nanoparticle lubricating materials;

[0146] 10 ml of anhydrous ethanol was added to 6 ml of the copper nanoparticle dispersion for dilution, and then 3 g of the mesoporous nano-silica obtained in step 1) and the diluted dispersion were placed in a three-necked flask and a constant pressure funnel respectively, and vacuum (vacuum degree is -0.1 MPa) was immersed for 4 hours, and then rotary evaporated for 6 hours to remove excess ethanol. The product was placed in a vacuum oven (vacuum degree is -0.1 MPa) and vacuum dried at 60°C for 12 hours to obtain a large-pore nano-silica composite material loaded with copper nanoparticles.

[0147] Performance Test:

[0148] 1) The performance of the macroporous nano-silicon dioxide composite material loaded with copper nanoparticles prepared in Example 4 was tested, and pure epoxy resin was used as a control group. The specific method was as follows:

[0149] 1.0 g of the macroporous nano-silica composite material loaded with copper nanoparticles was mixed with 10 g of epoxy resin while stirring, and then stirred at 45° C. for 1 hour to form a good suspension.

[0150] Then, 1.5 g of curing agent (triethylenetetramine) was added to the suspension, and after stirring for 5 minutes, vacuum defoaming treatment was performed, and then poured into a preheated mold (the mold preheating temperature was 60°C), cured at room temperature (25±5°C) for 2 hours, and then transferred to a vacuum oven (vacuum degree was -0.1 MPa) and cured at 80°C for 12 hours to obtain a polymer composite of epoxy resin and the large-pore nano-silica composite material; and then the tribological properties were tested using a ball-disc multifunctional friction and wear testing machine, and the test conditions were room temperature (25±5°C), a load of 15N, and a test time of 1 hour.

[0151] Test results:

[0152] Figure 7 The friction test results of pure epoxy resin and the polymer prepared in Example 4 are shown in Table 1. Figure 7 It can be seen that the average friction coefficient of pure epoxy resin is 0.63, and it does not change much over time. After adding the macroporous nano-silica composite material loaded with copper nanoparticles to the pure epoxy resin, the friction coefficient of the polymer is significantly reduced to 0.10 without obvious fluctuation.

[0153] 2) The hardness of the large-pore nano-silica composite material loaded with copper nanoparticles prepared in Example 4 was tested, and pure epoxy resin was used as a control group. The test was carried out according to the method in the national standard GB / T2411-2008. The specific method is as follows:

[0154] Place the sample on a hard horizontal plane, hold the hardness tester in a vertical position, and keep the tip of the pressure needle at least 9mm away from any edge of the sample. Immediately add the pressure seat to the sample without impact, make the pressure seat parallel to the sample and apply sufficient pressure. The pressure seat and the sample should be in close contact, and then read the indication of the indicating device.

[0155] Test results:

[0156] like Figure 8As shown, the hardness of the pure epoxy resin sample and the composite self-lubricating material prepared in Example 4 was tested using a microhardness tester. The results show that after the large-pore nano-silicon dioxide composite material loaded with copper nanoparticles was added to the pure epoxy resin, the hardness of the sample was significantly improved from HV21 to HV52. Copper nanoparticles and silica are both polymer reinforced fillers, which can improve the anti-friction and anti-wear properties of the epoxy resin by increasing its hardness.

[0157] 3) The contact angle test was performed on the large-pore nano-silica composite material loaded with copper nanoparticles prepared in Example 4, and pure epoxy resin was used as a control group. The test was performed with reference to the method in the national standard GB / T30693-2014. The specific method is as follows:

[0158] Place the sample on the sample stage of the instrument. Make sure the sample is placed flat without wrinkles or distortion. Hang a 5μl water droplet at the end of the needle. Raise the sample stage so that the sample surface contacts the suspended water droplet, then remove the sample to complete the transfer of the water droplet. Measure the contact angle within 60 seconds after the water droplet is transferred.

[0159] Test results:

[0160] like Fig. 9 As shown in the figure, through contact angle test, it was found that after adding large-pore nano-silica composite materials loaded with copper nanoparticles into epoxy resin, the contact angle of epoxy resin was reduced, which improved its wettability to water-based lubricants under wet friction conditions and was beneficial to the formation of lubricating film.

[0161] Example 5

[0162] Example 5 provides a large-pore nano-silicon dioxide composite material. The preparation method of the large-pore nano-silicon dioxide composite material in Example 5 is the same as that in Example 4. The difference between Example 5 and Example 4 is that:

[0163] Performance Test:

[0164] 1) When the performance of the macroporous nano-silica composite material loaded with copper nanoparticles prepared in Example 5 was tested, 2.0 g of the macroporous nano-silica composite material loaded with copper nanoparticles was mixed with 10 g of epoxy resin, and pure epoxy resin was used as a control group.

[0165] Test results:

[0166] Fig.10 The friction test results of pure epoxy resin and the polymer prepared in Example 5 are shown in Table 2. Fig.10It can be seen that the average friction coefficient of pure epoxy resin is 0.62, and it does not change much over time. After adding the macroporous nano-silica composite material loaded with copper nanoparticles to the pure epoxy resin, the friction coefficient of the polymer is significantly reduced to 0.06 without obvious fluctuations.

[0167] 2) The hardness of the large-pore nano-silica composite material loaded with copper nanoparticles prepared in Example 5 was tested, and pure epoxy resin was used as a control group. The test was carried out according to the method in the national standard GB / T2411-2008. The specific method is as follows:

[0168] Place the sample on a hard horizontal plane, hold the hardness tester in a vertical position, and keep the tip of the pressure needle at least 9mm away from any edge of the sample. Immediately add the pressure seat to the sample without impact, make the pressure seat parallel to the sample and apply sufficient pressure. The pressure seat and the sample should be in close contact, and then read the indication of the indicating device.

[0169] Test results:

[0170] like Fig.11 As shown, the hardness of the pure epoxy resin sample and the composite self-lubricating material prepared in Example 5 was tested using a microhardness tester. The results show that after the macroporous nano-silica composite material carrying copper nanoparticles was added to the pure epoxy resin, the hardness of the sample was significantly improved from HV21 to HV60, and as the content of nano-macroporous silica carrying copper nanoparticles in the epoxy resin increased, the hardness of the sample obtained in Example 5 also increased.

[0171] 3) The contact angle test was performed on the large-pore nano-silica composite material loaded with copper nanoparticles prepared in Example 5, and pure epoxy resin was used as a control group. The test was performed with reference to the method in the national standard GB / T30693-2014. The specific method is as follows:

[0172] Place the sample on the sample stage of the instrument. Make sure the sample is placed flat without wrinkles or distortion. Hang a 5μl water droplet at the end of the needle. Raise the sample stage so that the sample surface contacts the suspended water droplet, then remove the sample to complete the transfer of the water droplet. Measure the contact angle within 60 seconds after the water droplet is transferred.

[0173] Test results:

[0174] like Fig.12As shown in the figure, through the contact angle test, it was found that after adding the macroporous nano-silica composite material loaded with copper nanoparticles into the epoxy resin, the contact angle of the epoxy resin decreased. With the increase of the amount of silica composite material added, the contact angle tended to gradually decrease, indicating that the wettability of the epoxy resin to the water-based lubricant under wet friction conditions can be adjusted by adjusting the content of nano-macroporous silica loaded with copper nanoparticles in the epoxy resin.

[0175] Table 1 is a comparison of the mass of mesoporous nano-silica before and after adding liquid lubricant or solid nano-particle lubricating material in Examples 1-5.

[0176] Table 1

[0177]

[0178] Figure 3 Thermogravimetric diagrams of the oil-carrying macroporous nano-silicon dioxide composite materials obtained in Examples 1-3 are shown in FIG. Figure 3 It can be seen that the mesoporous nano-silica contains the injected lubricating additive (ionic liquid [DBUH + ][9C - ]、TIPAC 11 、[DBNH + ][18C - ]), and the loading amount of ionic liquid is basically consistent with the results in Table 1.

[0179] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A macroporous nano-silicon dioxide composite material, characterized in that: It comprises nano-sized large-pore silica and a lubricating additive loaded in the nano-sized large-pore silica; The nano-sized macroporous silica has a particle size of 50-110 nm and a pore size of 3-30 nm; The macroporous nano-silicon dioxide composite material is prepared from a silicon source, a template agent, a pore-enlarging agent, an organic amine catalyst, water, anhydrous ethanol, and a lubricating additive; The silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, trimethoxysilane and sodium silicate; The template agent is one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate and sodium dodecylsulfonate; The pore-enlarging agent is one or more of sodium salicylate, tributyl phosphate, and diethyl phthalate; The organic amine catalyst is one or more of octylamine, dodecylamine, ethanolamine, diethanolamine and triethanolamine; The lubricating additive is a liquid lubricant and / or a solid nanoparticle lubricating material.

2. The macroporous nano-silicon dioxide composite material according to claim 1, characterized in that: The liquid lubricant includes one or more of base oil, plant-based lubricating oil, ionic liquid, and perfluoropolyether lubricating oil; The solid nanoparticle lubricating material is one or more of copper nanoparticles, copper sulfide nanoparticles, molybdenum disulfide nanoparticles, and ferrosoferric oxide nanoparticles.

3. The macroporous nano-silicon dioxide composite material according to claim 1 or 2, characterized in that: The liquid lubricant is an ionic liquid [DBUH + ][9C - ]、TIPA C 11 or [DBNH + ][18C - ].

4. The method for preparing the large-pore nano-silicon dioxide composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Dissolving the template agent and the pore-enlarging agent in water and stirring the mixture at a certain temperature to obtain an organic composite template suspension; Adding an organic amine catalyst to the suspension, stirring and reacting for a period of time, adding a silicon source, stirring and reacting for a period of time, allowing the reaction system to naturally cool to room temperature, adding anhydrous ethanol, stirring and reacting for a period of time, and then standing to obtain a mixed solution; (2) centrifuging the mixed solution in step (1), washing and drying the solid product, and calcining it in a muffle furnace to remove the organic composite template, thereby obtaining mesoporous nano-silica; (3) Soaking or impregnating the mesoporous nano-silica and the solution of the lubricating additive or the dispersion of the lubricating additive under vacuum for a period of time, then removing the excess anhydrous ethanol by rotary evaporation, and drying to obtain a macroporous nano-silica composite material.

5. The preparation method according to claim 4, characterized in that: In step (1), the reaction temperature of the template agent and the pore-enlarging agent is 60-80°C, and the stirring reaction time is 0.5-2h; In step (1), the mass ratio of the silicon source to the template is 10-80:5-10; In step (1), the mass ratio of the silicon source to the pore expanding agent is 20-80:1-6; In step (1), the mass ratio of the silicon source to the organic amine catalyst is 20-75:1-3; In step (1), after adding the organic amine catalyst to the suspension, the stirring reaction time is 0.5 to 2 hours; the reaction temperature is 70 to 90°C; In step (1), after adding the silicon source to the suspension, the stirring reaction time is 1 to 4 hours; the reaction temperature is 70 to 90°C; In step (1), after the reaction system is naturally cooled to room temperature, when anhydrous ethanol is added, the mass ratio of anhydrous ethanol to silicon source is preferably 4-20:1-3; and the stirring reaction time after adding anhydrous ethanol is 0.5-1h.

6. The preparation method according to claim 4, characterized in that: In step (2), washing is performed with water and / or anhydrous ethanol; In step (2), washing with anhydrous ethanol is performed under centrifugal conditions; In step (2), washing is performed under centrifugal conditions; In step (2), the drying temperature is 50-90°C and the drying time is 10-24h; In step (2), the calcination temperature is 450-650°C; In step (2), the time is started when the temperature reaches the calcination temperature, and the calcination time is 3 to 7 hours.

7. The preparation method according to claim 4, characterized in that: In step (3), the solution of the lubricating additive or the dispersion of the lubricating additive is an anhydrous ethanol solution of the lubricating additive or an anhydrous ethanol dispersion of the lubricating additive; the mass ratio of the mesoporous nano-silica to the solution of the lubricating additive is 1:0.5~10; the ratio of the mesoporous nano-silica to the dispersion of the lubricating additive is 1g:(1.5~8)mL.

8. The preparation method according to claim 7, characterized in that: In step (3), the concentration of the solution of the lubricating additive is 2-8% (w / v); the concentration of the dispersion of the lubricating additive is 0.1-0.5 g / mL.

9. The preparation method according to claim 4, characterized in that: In step (3), the immersion method is vacuum immersion, the vacuum degree of the vacuum immersion is -0.08 to -0.1 MPa; the immersion temperature is room temperature, and the immersion time is 3 to 6 hours; In step (3), the impregnation method is vacuum impregnation, the vacuum degree of the vacuum impregnation is -0.08~-0.1MPa; the impregnation temperature is room temperature, and the impregnation time is 3~6h; In step (3), the drying temperature is 50-80° C. and the drying time is 8-24 hours.

10. Use of the large-pore nano-silicon dioxide composite material according to any one of claims 1 to 3 in the preparation of lubricants for the automotive industry or high-end equipment.

Citation Information

Patent Citations

  • Boron-doped silicon dioxide microsphere with hierarchical pore structure as well as preparation method and application of boron-doped silicon dioxide microsphere

    CN116715246A

  • Preparation method of silicon dioxide material with hierarchical pore structure

    CN110759348A

  • Solid-liquid phase composite lubricating material as well as preparation method and application thereof

    CN115948191A

  • Dendritic silicon dioxide oil-containing material as well as preparation method and application thereof

    CN117987191A